Broken [large type] : a novel - Slaughter, Karin, 1971- (Thorndike Press large print core, 2010)
When Special Agent Will Trent arrives in Grant County, he finds a police department determined to protect its own and far too many unanswered questions about a prisoner's death. He doesn't understand why Officer Lena Adams is keeping secrets from him. He doesn't understand her role in the death of Grant County's popular police chief. And he doesn't understand why that man's widow, Dr. Sara Linton, needs him now more than ever. (Bestseller)